Communication networks and systems for power utility automation. Specific communication service mapping (SCSM). Mappings to MMS (ISO 9506-1 and ISO 9506-2) and to ISO/IEC 8802-3 Part 8-1, (11th May 2020) - British Standards Institution,
No abstract available